The review of natural products. - Facts and Comparisons (Firm). (St. Louis, Mo. Facts and Comparisons, 2000)
Contains detailed information about natural products, including their botany, history, chemistry, pharmacology, medicinal uses, toxicology, and patient information. Includes significantly documented drug interactions. Also features a Web-link to PubMed.
Title from initial screen.
Available also in print and online.
Keywords: Pharmacognosy -- Periodicals; Natural products -- Therapeutic use -- Periodicals; Materia medica -- Periodicals; Plant Extracts; Phytotherapy; Pharmacognosy; Materia Medica; Review Literature